Pre-Columbian cultivation of vegetatively propagated and fruit tree tropical crops in the Atacama Desert - Capriles, José M.; García, Magdalena; Valenzuela, Daniela; Domic, Alejandra I.; Kistler, Logan; Rothhammer, Francisco; Santoro, Calogero M. (Frontiers in Ecology and Evolution, 2022)
South America is a megadiverse continent that witnessed the domestication, translocation and cultivation of various plant species from seemingly contrasting ecosystems. It was the recipient and supplier of crops brought to and from Mesoamerica (such as maize and cacao, respectively), and Polynesia to where the key staple crop sweet potato was exported. Not every instance of the trans-ecological expansion of cultivated plants (both domesticated and wild), however, resulted in successful farming. Here, we review the transregional circulation and introduction of five food tropical crops originated in the tropical and humid valleys of the eastern Andes—achira, cassava, ahipa, sweet potato, and pacay—to the hyper-arid coastal valleys of the Atacama Desert of northern Chile, where they have been found in early archaeological sites. By means of an evaluation of the contexts of their deposition and supported by direct radiocarbon dating, stable isotopes analyses, and starch grain analysis, we evaluate different hypotheses for explaining their introduction and adaptation to the hyper-arid soils of northern Chile, by societal groups that after the introduction of cultigens still retained a strong dependence on marine hunting, gathering and fishing ways of life based on wide variety of marine coast resources. Many of the studied plants were part of a broader package of introduced goods and technological devices and procedures, linked to food, therapeutic medicine, social and ritual purposes that transformed previous hunter-gatherer social, economic, and ideological institutions. Based on archaeological data, we discuss some of the possible socio-ecological processes involved in the development of agricultural landscapes including the adoption of tropical crops originated several hundred kilometers away from the Atacama Desert during the Late Holocene.